Osteoporosis in childhood: related factors and prevention (Colombia Medica, 2024)
Osteoporosis is defined as a reduction in bone mass. This loss is more important in states of malnutrition, physical inactivity, and with a poor dietary intake of vitamin D and calcium. Bone mineralization depends on both genetic and nutritional factors, as well as endocrine, metabolic, and mechanical factors. Several studies in children have shown that the development of osteoporosis in adulthood may be influenced by the nutritional status during childhood, especially with regard to the contributions of calcium and vitamin D. However, currently there are many questions regarding its pathogenesis and diagnosis and its treatment, some of which are reviewed in this paper. The aim of this work has been to provide an update on the main factors associated with the development of osteoporosis and its prevention in infancy.